Rhythm and movement in developmental age - Liparoti, M.; Minino, R. (Journal of Human Sport & Exercise, 2021)
Coordination is the neurophysiological activity of regulating the synchronism and extent of contraction and relaxation of the various muscles in order to achieve more or less complex movements in pursuit of set goals. Coordinated gestures are characterised by a correct rhythm of movement. The relationship between Movement and Rhythm, is of extreme importance for several reasons. On a biological level, rhythmic capacity leads to a reduction in muscular fatigue, frees us from unnecessary effort, and optimises movement by reducing energy expenditure. Furthermore, rhythmicity develops a series of motor and cognitive skills, which are fundamental for improving the activities of daily life of everyone. The purpose of this work was to investigate articles in the literature that explore the relationship between rhythmicity and motor and cognitive development in school-aged children, and the benefits of improving this motor skill. It has been widely demonstrated that rhythmic training improves coordination, sense of direction, laterality and organisation of space and time, reading, language, logical and mathematical thought structure and socialisation. The development of this special coordinative ability has also been shown to be crucial in children with learning disabilities and in neurodevelopmental disorders. Therefore, education and training in Rhythm is fundamental for learning motor and cognitive development throughout each child's developmental years.